Hybrid and Collaborative Networks Approach: Online Learning Integrated Project and Kolb Learning Style in Mechanical Engineering Courses - Jalinus, Nizwardi; Ganefri; Zaus, Mahesi Agni; Wulansari, Rizky Ema; Nabawi, Rahmat Azis; Hidayat, Hendra (International Journal of Online and Biomedical Engineering (iJOE), 2022)
Engineering education is very important to prepare quality graduates. An alternative hybrid and collaborative networks approach in learning is the current choice. This study aims to explain the online learning integrated project and Kolb learning style in mechanical engineering courses to enhance students' academic achievement which is implemented through a hybrid and collaborative networks approach. The research method used is a quantitative approach with the posttest control group design method. We carry out learning activities using Project and Kolb Learning on higher education students from Mechanical Engineering Education who take part in learning this project. Students who participate are limited to small groups, which are divided according to their learning styles groups, and the implementation is carried out in a hybrid and collaborative through e-learning and face-to-face. Collecting data using Kolb Learning Styles Inventory, and achievement test. While the data analysis used descriptive analysis and one-way Anova with the help of SPSS software. The results of this study indicate that there is a difference in the average academic achievement of students based on the four learning style groups, and the thinker learning style group has the highest average academic achievement among the four. The selection of appropriate learning styles and learning models has an impact on optimal and effective academic achievement.